Can the establishment of free trade zones promote the internationalization of enterprises? - Evidence from micro-enterprise level. - Jijun Zhang; Haowei Wang (PLoS ONE)
Based on microdata of A-share listed companies in Shanghai and Shenzhen from 2009 to 2022 as research samples, this paper takes the implementation of Free Trade Zones policy as the starting point and using the difference in differences method to analyze the impact of the establishment of Free Trade Zones on the internationalization level of enterprises. The empirical results indicate that (1) Free Trade Zones policysignificantly improved enterprises' internationalization level, and the conclusion still holds after a series of endogeneity and robustness tests. (2) Mechanism analysis showedthat digital transformation, resource allocation efficiency, and green innovation are intermediary variables affecting enterprises' internationalization levels in Free Trade Zones. The establishment of Free Trade Zones can promote digital transformation, resource allocation efficiency, and green innovation of enterprises, thereby enhancing their internationalization level. (3) Heterogeneity analysis found that establishing free trade experiments has a more significant effect on improving the internationalization level of enterprises in low city levels, large-sized companies, capital-intensive and technology-intensive companies, businesses with executives who have overseas experience, and high-tech companies (4) Further research has found that the establishment of Free Trade Zones also has a positive spatial spillover effect on enterprises in surrounding cities. The above conclusion enriched and expanded the research on the impact of the establishment of Free Trade Zones on the internationalization level of enterprises and has important practical significance for enhancing the competitiveness of enterprises.